Endovascular management of ruptured common iliac mycotic aneurysm in an HIV-positive patient. (5th August 2013) - Aziz, Aamir; Mooka, Busi; Clarke Moloney, Mary; Kavanagh, Eamon
Abstract : Isolated iliac artery aneurysms are a rare entity. The majority of cases are asymptomatic and often escape detection. Mortality rates after sudden rupture and emergent surgery for iliac artery aneurysm are very high. We report a case of a 56-year-old man who presented with right hip pain masquerading as septic arthritis or psoas abscess. CT showed ruptured right common iliac artery aneurysm with extensive active extravasation into psoas with a retroperitoneal haematoma. Aneurysm was repaired using an endovascular technique. Postoperative recovery was eventful with the patient experiencing severe back pain radiating down the leg accompanied with fever. CT showed persistent, right iliopsoas haematoma and pelvic haematoma with secondary hydronephrosis. Viral screen for hepatitis B, C and HIV returned positive. The patient was started on intravenous meropenem. Fever and pain settled. Repeated CT scan showed decrease in retroperitoneal pelvic haematoma.